2023
DOI: 10.1038/s41598-023-31884-2
|View full text |Cite
|
Sign up to set email alerts
|

A laminar forced convection via transport of water–copper–aluminum hybrid nanofluid through heated deep and shallow cavity with Corcione model

Abstract: The article explores how fluid flows and heat transfers in both deep and shallow cavities when using a nanofluid made of water, copper, and aluminum oxide. The study applies the Corcione model to hybrid nanofluids, which considers viscosity, conductivity, and the size of the nanoparticle, temperature, and Reynolds number. The cavity is connected to a rectangular channel, with the cavity's length being half the total length of the enclosure, and the aspect ratio (cavity height divided by height of the channel) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These are the basic variables that are obtained after the numerical solution. Then, a post-processing procedure is started to calculate the computational values given below: 6–8,10,12,13…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the basic variables that are obtained after the numerical solution. Then, a post-processing procedure is started to calculate the computational values given below: 6–8,10,12,13…”
Section: Problem Formulationmentioning
confidence: 99%
“…To determine the convection properties of hybrid nanofluids in heated deep and shallow cavities, numerical research was carried out in ref. 12 . This study employed the Corcione nanofluid model, which was developed using Comsol 5.6, a program that is based on the finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…Research on nanofluids has shown great potential for optimizing heat transfer behavior in mixed convection systems within ventilated cavities. By studying the effect of nanoparticle density and comparing the performance of nanofluids with that of pure water with respect to heat transfer properties, it has been shown that nanofluids represent a promising means of enhancing heat transfer efficiency in engineering applications [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Motile microorganisms are added with the dilute suspension of nanoparticles in the base fluid to enhance mass transfer, microscale mixing, to improve nanofluids stability, and to prevent nanoparticle agglomeration in nanofluids [2]. It has been discovered that the nanofluids and hybrid nanofluids have a substantial influence on fluid velocity, temperature, skin friction, and heat transfer rates under different models and situations [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%